Closure - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2021)
Journal of Infrastructure & Facility Asset ManagementVolume 3, Issue 3, December 2021                                           (e) ISSN 2656-8896 (P) ISSN 2656-890XJIFAM, Vol.3, Issue 2, August 2021Neighborhood for Adolescent Girls: The Case of  Urban Dense Kampong In Yogyakarta City Center           Mu’afifah & SetiawanCengklik Reservoir Tourism Development with approach Eco-WaterfrontAuliya Rohmah Ramadhani, Budi Prayitno & Wiwik SetyaningsihEarly Chinese Settlements Adaptive Reuse as History and Activity Node at Lasem Living MuseumArdelia J. Cungwin & Widjaja MartokusumoImprovement Strategy for KOTAKU program in Slum Settlements Area in SidoarjoRirin Putri Kusuma & Dian RahmawatiUrban Resilience: How to Apply in the Planning and Design Practice?Novi Maulida Ni’mah & Bakti Setiawan JIFAM, Vol.3, Issue 1, March 2021Framework for Facilities Management Services Procurement in Public Buildings in Abuja-NigeriaSani Momoh, Jennifer Ayegba, Luqman Oyewobi, Calistus Ayegba, Abdulquadri Bilau & Richard JimohHydropower Sustainability Assessment Protocol (HSAP) Implementation in Indonesia: A mini-reviewNovi Andriany Teguh & Ainul Firdatun NisaaWeighting The Fire Protection Systems Technical Requirements to Determine Flats Reliability Against Fire HazardsAris Aminulwahyu, I Putu Artama Wiguna & Tri Joko Wahyu AdiPurabaya Bus Station Service Performance in New Adaptation PeriodPutu Cinthya Pratiwi Kardita, Achmad Wicaksono & M. Ruslin AnwarModeling and Optimization of the Compressive Strength of High Volume Fly Ash ECC with Low Modulus PVA Fiber Using Response Surface Methodology (RSM)Isyaka Abdulkadir & Bashar S. MohammedImplementation of Risk Management in Property ProjectsI Wayan Muka & Agung WibowoA New Approach to Estimate the Potential Assets Loss due to Dam-Break Event in IndonesiaFarrell Wiguna, Doddi Yudianto, Bobby Minola Ginting & Albert Wicaksono